KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENANGGULANGAN TINDAK PIDANA MELALUI PENYELESAIAN SECARA NON LITIGASI - Alisan Alisan (SOL JUSTICIA, 2018)
The law that applies to this society, because of experiencing developments following the development of life, then makes the law very diverse. So that the law can be assessed from various specific aspects. Therefore, when viewed from the aspect of its function, one of the scope of public law is criminal law which can basically be divided into material criminal law (materelel strafrecht) and formal criminal law (Formeel Strafrecht / Strafprocesrecht). related literature and books. the problem taken is How is the criminal law policy in the handling of criminal acts through efforts to resolve outside the current positive legal process? and What is the criminal law policy in the handling of criminal acts through efforts to resolve outside the process in the context of renewing criminal law in Indonesia? The results obtained from the study are that criminal law policy in the handling of criminal acts through efforts to resolve outside the positive legal process is currently only a small part, while all of which are still oriented towards formal solutions. Criminal law policy in the handling of criminal acts through efforts to resolve outside the process in the context of renewal of criminal law in Indonesia should be regulated in an integrated manner, and a criminal type that can compromise or take advantage of positive aspects is needed (the opposite also means, avoiding negative aspects) of imprisonment in a party and criminal supervision on the other hand. So compromise "criminal" with "action". In order to bring equitable justice.